Emergent Literacy Skills in English-Speaking Preschoolers with Suspected Childhood Apraxia of Speech: A Pilot Study. - Lefebvre, Pascal; Gaines, Robin; Staniforth, Laurie-Ann; Chiasson, Véronique (Canadian Journal of Speech-Language Pathology & Audiology)
This study piloted a sample protocol to assess phonological awareness, print awareness, and handwriting readiness in eight 4- to 5-year-old children suspected of having childhood apraxia of speech (CAS) by their speech-language pathologists. These children's performance on the protocol is described and compared to that of age-and gender-matched peers with typically developing speech, language, and motor skills. All participants with suspected CAS demonstrated some difficulties in phonological awareness, print awareness, or handwriting readiness. As a group, participants with suspected CAS performed significantly more poorly than their typically developing peers on rhyme awareness, print awareness, letter knowledge, hand grasp, and motor coordination. These results highlight the importance of including a broad set of emergent literacy skills, in addition to speech production, when assessing preschoolers with suspected CAS and in intervention, if warranted.